Anamaria Babiaș-Ciobanu, "Jon Fosse and the New Theatre", Cluj Napoca: Școala Ardeleană, 2020, 330 p. - LĂȚUG, Diana (Studia Universitatis Babeș-Bolyai Philologia, 2023)
Jon Fosse and the New Theatre is the title of an ample research on the Norwegian author, done by PhD student Anamaria Babiaș-Ciobanu (b. 1987). She held her public defence in Philology in 2018, under the supervision of Professor Sanda Tomescu Baciu, at the Faculty of Letters, Babeș-Bolyai University, followed by the publication of the present volume, based on the PhD thesis with the same title. Prior to this she also translated Jon Fosse’s Shadows (Skuggar) into Romanian, under the title Umbre (Casa Cărții de Știință, 2015). Furthermore, Babiaș-Ciobanu has published several corresponding articles in the academic journal Studia Universitatis Babeș-Bolyai Philologia: “A Short Example of Jon Fosse’s Dramaturgy. Play Sov du vesle barnet mitt” (vol. 59, no. 1, pp. 87-99, 214) or ”From Ibsen to Beckett: Aspects of the Human Condition” (vol. 60, no.1, pp. 133-147, 2015). Her MA thesis tackles the theme of the latter article and her BA thesis was focused on Norwegian dramaturgy as well: “Løgn og sannhet i Ibsens Vildanden” (The Concepts of Lie and Truth in Ibsen's The Wild Duck). Thus, Babiaș-Ciobanu has displayed a continuous interest in this field and has extensively contributed to spreading the Fosse’an universe on Romanian soil.